JIHAD SASTRA: ANALISIS HERMENEUTIKA PAUL RICOEUR PADA NOVEL PENAKLUK BADAI KARYA AGUK IRAWAN MN - Barokah, Sulih Nur; Arsam; Saputro, Dedy Riyadin; Ulul Aedi (Jurnal Dakwah Tabligh, 2022)
Jihad is not always by taking up arms and going to war. Today, jihad is perceived and practiced in a variety of approaches. One of them is with literary works. The use of literary works as a medium for proselytizing has recently been widely loved because the message conveyed through the text indirectly affects the reader. Thus, the purpose of this study is to identify the meaning of jihad through literary works. The object of this study is the novel Conqueror of the Storm by Aguk Irawan MN which is considered appropriate to be used as a source related to jihad. This research uses Paul Ricoeur’s hermeneutic theory and methods, namely objective, reflective, and existential. The results of the text analysis were obtained through three stages, namely objectively, and reflectively, to extensively produce 3 meanings of jihad, namely jihad meaning proselytizing, science, and meaning physical jihad. Jihad means proselytizing is related to the enforcement of Amar Makruf Nahi Munkar, jihad is jihad to become mujtahid, and jihad means physical is the jihad of love of the homeland in defending sovereignty.